Mobile-Assisted Language Learning (MALL) for grammar: Trends and outcomes (2018-2023) - Muslimah, Nadrotul; Tarihoran, Nafan; Oktafiana, Fadilla (Journal of English Language Teaching and Learning (JETLE), 2025)
Mobile Assisted Language Learning (MALL), especially in grammar skills, may have a favorable impact on the teaching and learning process as industrial technology 4.0 advances. Thus, this systematic review analyzed the trends and the outcomes of Mobile Assisted Language Learning MALL in teaching grammar from a diverse range of studies. This study was conducted by using Publish or Perish software to compile the data and VOSviewer to generate the data visualization and report in bibliometric analysis in the last 5 years (2018-2023), with exclusion and inclusion criteria considered. A total of 149 articles were excluded as criteria, and 15 selected articles were systematically analyzed. The analysis highlighted the outcomes of Mobile Assisted Language Learning (MALL), such as interactive learning experiences. The finding implied that the students' grammar skills were positively impacted due to the use of mobile applications such as Duolingo, Anki, Telegram, Throwback Time (TBT), and other tools. Besides, it also influenced students' interest in the teaching-learning process, which tended to increase students' engagement, since it can save time, energy, and money. However, there was a need to develop more adjustments and useful features to deal with some challenges in teaching and learning grammar using MALL. It is therefore suggested that future research focus on the challenge and approach to teaching grammar using MALL or mobile learning.